Effect Of Soaking in Liquid Smoke on the Specific Gravity Of Gerungang Wood (Cratoxilon Arborences) in the Radial Direction: Pengaruh Perendaman dalam Asap Cair terhadap Berat Jenis Kayu Gerungang (Cratoxilon Arborences) dalam Arah Radial - Wahyu Supriyati; Alpian Alpian; Chuchita Chuchita; Efriyana Oksal; Zimon Pereiz; Aprilian Wanashalom (JURNAL HUTAN TROPIKA, 2026)
The objective of this study was to determine the effect of immersion in different liquid smoke treatments on the specific gravity of Gerunggang wood at the radial direction. The study was conducted at the Forest Products Technology Laboratory, Faculty of Agriculture, Forestry and Fisheries Palangka Raya University. The parameter observed was the specific gravity of the wood. The experimental method used was a 2x2 factorial completely randomized design (CRD) with two treatments: liquid smoke concentration (0%, 5%) and radial location (near the heart and near the bark), with 10 replications. The results of this study showed that immersion in liquid smoke had a not significant effect (p<0.05) on the specific gravity. The influence of the radial position was significantly different, where the part near the liver was higher than the part near the skin. The interaction between the immersion factor and the radial position had no significant effect.